Oxidative Cleavage of Alkene C=C Bonds Using a Manganese Catalyzed Oxidation with H2O2 Combined with Periodate Oxidation. Issue 42 (31st October 2019) - Mecozzi, Francesco; Dong, Jia Jia; Angelone, Davide; Browne, Wesley R.; Eisink, Niek N. H. M.
Abstract : A one‐pot multi‐step method for the oxidative cleavage of alkenes to aldehydes/ketones under ambient conditions is described as an alternative to ozonolysis. The first step is a highly efficient manganese catalyzed epoxidation/ cis ‐dihydroxylation of alkenes. This step is followed by an Fe(III) assisted ring opening of the epoxide (where necessary) to a 1, 2‐diol. Carbon–carbon bond cleavage is achieved by treatment of the diol with sodium periodate. The conditions used in each step are not only compatible with the subsequent step(s), but also provide for increased conversion compared to the equivalent reactions carried out on the isolated intermediate compounds. The described procedure allows for carbon–carbon bond cleavage in the presence of other alkenes, oxidation sensitive moieties and other functional groups; the mild conditions (r.t.) used in all three steps make this a viable general alternative to ozonolysis and especially for use under flow or continuous batch conditions. Abstract : A one‐pot multi‐step method for the oxidative cleavage of alkenes to aldehydes/ketones under ambient conditions is reported. Combining a highly efficient manganese catalyzed epoxidation/ cis ‐dihydroxylation with Fe(III)(ClO4 )3 assisted ring opening is followed by periodiate cleavage of the resulting diol.